Development of Powtoon Media in IPAS Learning Assisted by The PBL Model in Fourth Grade Elementary School - Chindy Yuginta Wanti; Hadiyanto; Desyandri; Yeni Erita (Postgraduate, University of Mataram, 2024)
Learning is still carried out conventionally, even though school facilities support carrying out learning using renewable technology-based learning media. However, teachers lack innovation in learning media to be used in the learning process. Apart from that, student learning outcomes are still low. This research aims to develop Powtoon learning media assisted by the problem-based learning model in science and science learning in class IV elementary schools that is valid, practical, and effective. This type of research is research and development (R&D). The development model used is ADDIE. The methods used to collect research data are observation, interviews, questionnaires, and learning outcomes tests. Subject validation is carried out by material, language, and media expert validators. The test subjects were Class IV elementary school students and class teachers. The validation results by material, media, and language experts stated that they were valid for the media being developed. The practicality results in both small and large groups obtained a very valid practicality category. Meanwhile, the results of effectiveness tests in small and large groups have increased. In this way, the media developed is declared valid, practical and effective, and suitable for use in science and science learning in Class IV.